AN MPI-BASED FRAMEWORK FOR PARALLEL PROCESSING OF INTEGRATED CIRCUITS LAYOUT IMAGES - Otwagin, Aleksej; Doudkin, Alexander (International Journal of Computing, 2014)
We consider basic algorithms and processing technologies for integrated circuit layout images. The images represented as a set of frames can regard as a dataflow and the processing are perfectly suited for parallel implementation. We propose a framework architecture for designing parallel systems of image dataflow processing. The framework uses the algorithm of a virtual associative network for increasing processing speed and system throughput during runtime.